The Teacher’s Strategies in Teaching English Productive Skills - Abdul Malik Azis; Endang Susilawati; Dwi Riyanti (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
The purpose of this research is to found out the strategies applied by the English teacher in MAN 01 Kubu Raya. This research also has a purpose to identify how the teacher apply the strategies in the planning phase also in the implementation phase. The research is using descriptive qualitative method with observation and interview to collect the data. The subject of the research is one teacher in MAN 01 Kubu Raya. The research found the strategies that the teacher use is divided into two phase such as planning and implementation. In the planning, the teacher applying the strategies such as identifying situational factors, establishing learning goals, creating feedback and assessment procedures, choosing teaching or learning activities, and integration. In the implementation phase, the teacher used different strategies in teaching speaking and writing. In speaking, the teacher used discussion, simulations and role play, presentation, and question and answer with the addition of summarization, meanwhile, in teaching writing, the teacher used the strategies make a lesson visual, summarization, collaborative learning, modify vocabulary, sentence combining, study of models, and provide comprehensible input. This is showing that the teacher is using strategies in teaching English productive skills. The researcher concluded that the teacher strategy that had been used by one of the teachers at MAN 01 Kubu Raya already existed and the steps used by the teacher when teaching productive skills were very clear and could be found in the lesson plan and in the classroom.